Low frequency oscillations in summer monsoon rainfall over India - CHOWDHURY, A; MUKHOPADHYAY, RK; RAY, KCSINHA (MAUSAM, 1988)
The paper deals with spatial and temporal variations of different frequency modes of the southwest monsoon rainfall over India. Daily normal rainfall data (1901-1970) and that of the individual years for the period 1978-1983 for 220 well distributed stations throughout the country are subjected to harmonic analysis to investigate the contributions of different frequency modes. The results reveal the presence of 30-60 day periodicities as a predominant mode over central Peninsula in the long term normal as well as individual years. The variance explained by the 10.20 days oscillations exceed that of 30-60 days over central India during the good monsoon years. In good monsoon years the fundamental mode is predominant north of about 25° N while during the bad monsoon years it extends to more southern latitudes.